2016
DOI: 10.1016/j.thromres.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric post-thrombotic syndrome in children: Toward the development of a new diagnostic and evaluative measurement tool

Abstract: Objective: Our goal was to conduct the generation and piloting of a discriminative and evaluative tool for pediatric post-thrombotic syndrome.Methods: We followed a formative model for the development of the tool, focusing on the signs/symptoms (items) that define post-thrombotic syndrome. For item generation, pediatric thrombosis experts and diagnosed with extremity post-thrombotic syndrome during childhood nominated items. In the piloting phase, items were cross-sectionally measured in children with limb dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In a previous study we showed that PODCI, which measures activities and participation in children, might be a reasonably good approximation to assess the impact of PTS on the lower extremities. However, PODCI was not sensitive enough to measure the impact of PTS on the upper extremities . This is likely due to the fact that children with impaired endurance may find that most of the activities listed in PODCI for the evaluation of upper extremities are easy to perform.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study we showed that PODCI, which measures activities and participation in children, might be a reasonably good approximation to assess the impact of PTS on the lower extremities. However, PODCI was not sensitive enough to measure the impact of PTS on the upper extremities . This is likely due to the fact that children with impaired endurance may find that most of the activities listed in PODCI for the evaluation of upper extremities are easy to perform.…”
Section: Discussionmentioning
confidence: 98%
“…However, PODCI was not sensitive enough to measure the impact of PTS on the upper extremities. 13 This is likely due to the fact that children with impaired endurance may find that most of the activities listed in PODCI for the evaluation of upper extremities are easy to perform. In contrast, some of the activities listed for the evaluation of lower extremities are more challenging and require better endurance.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of study enrollment, 2 assessors measured PTS signs applying the clinician assessment component of CAPTSure, which includes the assessment of thigh and calf circumference difference and ulcers for the lower extremity and arm circumference difference and collaterals for the upper extremities (Appendix S1). Assessors took 3 measurements, as previously described, and averaged the obtained values to determine limb circumference difference. In addition, the assessor evaluated pain intensity in children aged 4 to 9 years using the Faces Pain Scale–Revised (FPS‐R) .…”
Section: Methodsmentioning
confidence: 99%
“…The index for the Clinical Assessment of PTS (CAPTSure) is a tool developed for the diagnosis and severity rating of PTS in children . Whereas PTS signs are measured by the clinician using a clinician assessment component, PTS symptoms are reported by either the patient or their proxy, according to the age of the child being assessed, using a patient/proxy questionnaire component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation